2018
DOI: 10.4081/ija.2018.1295
|View full text |Cite
|
Sign up to set email alerts
|

Compost enriched with ZnO and Zn-solubilising bacteria improves yield and Zn-fortification in flooded rice

Abstract: Zinc (Zn) is an essential element for humans, animals and plants, however, its deficiency has been widely reported around the world especially in flooded rice. Adequate amount of Zn is considered essential for optimum growth and development of rice. We hypothesised that management practices like Zn-mineral fertiliser, -compost, and -solubilising bacteria would improve Zn availability and uptake in flooded rice. A series of studies were conducted to find out the comparative efficacy of Zn-enriched composts (Zn-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 25 publications
1
16
0
Order By: Relevance
“…The yield parameters such as grains yields and biomass production increased significantly with the application of Zn and the maximum increase was recorded with the application of 1.5% bio-activated Zn coated urea. Our results are in line with Zeb et al [20] who reported improved yield parameters with the application of Zn. Grain production is an important parameter contributing towards yield, with the application of Zn, a significant increase in grain yield of wheat was observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The yield parameters such as grains yields and biomass production increased significantly with the application of Zn and the maximum increase was recorded with the application of 1.5% bio-activated Zn coated urea. Our results are in line with Zeb et al [20] who reported improved yield parameters with the application of Zn. Grain production is an important parameter contributing towards yield, with the application of Zn, a significant increase in grain yield of wheat was observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Before using inoculum, an optical density of 0.5 at 535 nm was maintained with 10 8 -10 9 colony-forming units (CFU) mL −1 . This suspension (inoculum) of the bacterial strain was used for urea coating to prepare bio-activated Zn coated urea [20]. Briefly, powdered organic material (plant residues) was first dried in an oven at 80 • C, inoculated with bacterial strain AZ6, and incubated for 72 h at 30 ± 1 • C in an incubator.…”
Section: Preparation Of Different Urea Formulationsmentioning
confidence: 99%
“…MN13 caused the highest increase in physiological parameters, as compared to the normal and Ni stressed soil. This increase might be attributed to the plant-microbe interactions which help improve micro-as well as macronutrients through various mechanisms such as the exudation of siderophores [77][78][79][80]. This premise is supported by the data presented in (Figure 2), showing a significant increase in the concentration of Fe and Zn in sesame tissues.…”
Section: Discussionmentioning
confidence: 53%
“…Zinc plays a major role in the development of tiller buds in rice plants; the meristem tissue requires 10 times more Zn than mature leaf blades for the functions of cell division and elongation, and thus Zn deficiency can inhibit tiller formation [ 42 , 43 ]. Zn fertilizer enhances photosynthesis through improving the photosynthetic rate and by increasing the chlorophyll content as well as the translocation of photosynthates to the grain [ 44 , 45 , 46 ]. Thus, applying soil Zn at the early growth stage is more efficient for boosting yield formation than the foliar Zn application in the later stage.…”
Section: Discussionmentioning
confidence: 99%